Eating disorder and metabolism in narcoleptic patients - Chabas, Dorothée; Foulon, Christine; Gonzalez, Jesus; Nasr, Mireille; Lyon-Caen, Olivier; Willer, Jean-Claude; Derenne, Jean-Philippe; Arnulf, Isabelle (Sleep (New York, N.Y.), 2007)
To evaluate eating behavior and energy balance as a cause of increased body mass index (BMI) in narcolepsy. Case controlled pilot study. University hospital. 13 patients with narcolepsy (7 "typical" patients, with HLA DQB1*0602 and clear cut cataplexy, with suspected hypocretin deficiency; and 6 "atypical" narcoleptics, i.e., HLA negative or without cataplexy), and 9 healthy controls matched for age, gender, and ethnicity. Energy balance was evaluated by measuring BMI, rest energy expenditure with calorimetry, daily food and water intake, and plasma hormone levels. Eating behavior was evaluated using psychometric tests (EAT-40, EDI2, CIDI-2, MADRS). Patients with narcolepsy (whether typical or not) tended to be overweight and to have a lower basal metabolism than controls. Only patients with typical narcolepsy tended to eat less than controls. Narcoleptic patients who were overweight ate half as much as others, indicating caloric restriction. Plasma glucose, cortisol, thyroid, and sex hormones levels did not differ between groups, while prolactin levels were twice as high in patients with narcolepsy as in controls. Narcoleptic patients had higher EAT-40 scores and more frequent features of bulimia nervosa (independent of depressive mood) than controls, suggesting a mild eating disorder, classified as "Eating Disorder Not Other Specified." Both lower basal metabolism and subtle changes in eating behavior (rather than in calorie intake) could explain the positive energy balance leading to overweight in narcolepsy. Eating behavior changes may be a strategy to control weight or to avoid daytime sleepiness.